Upaya Penjaminan Mutu Pendidikan Melalui Akreditasi Sekolah Di 9 SDN Di Wilayah Kabupaten Lamongan - Zainal Aqib (Jurnal Pendidikan Islam, 2019)
Abstract: Expedient in progress the National Education Quality in a order to hoped that suitable with “UU No. 20 Th 2003” about the National Education system, need to do improving all at once to constructive. The control education quality system, that given with pass acridity. Acridity be held for constant the proper of program and school education unite in every ladder and kind of education. Acridity to program and education unite be held by national acridity board. Based above, is “what with have school acridity can guarantee education quality in the nine SDN in Lamongan regency?” The direction of observation is to give information about the popper of school or program that to do standard national education. If advantage that hoped from this result of PTS like statement for school at expedient improving quality and program of improving school. The observation be held at 9 SDN at July 2009 with use acridity instrument from BAN S/M. The observation file be analysis based penscoran technique and progress the result of acridity. This result of PTS is show there is improving value, from sickles 1 and sickles II. The finally result show if the value acridity of 9 SDN, it is about 71-85 with acridity average B. To headmaster, you must constant can improving result acridity four years later.